India's 1999 elections and 20th century politics/ edited by Paul Wallace (New Delhi, 2003)
This book examines the consequences and results of the 1999 general elections in light of the recent developments in Indian politics and the Indian party system.
Keywords: "Political science, Elections-India, Wallace,Paul, Roy, R"